Verificación de bacterias de transmisión hídrica después de la utilización de materiales locales como lechos filtrantes - Denisse Iveth, Cadena Samaniego (2020)
Bacterias are cosmopolitan microorganisms that are throughout the world, and they live in different media such as food, air, water, among others. They are carried mainly by water; this is the need for research, the objective of which was to verify the bacteria of water transmission after the use of local materials such as filter beds, which, due to their different porosity, provide the retention of both cocci and bacillus microorganisms based on its size, applying seeding, cultivation, and identification techniques. It was a fact that within the intermediate range if there is bacterial growth ≥100 CFU / 100ml according to the World Health Organization, the efficacy is not 100%. In terms of water purification with the use of diatomaceous earth of Guayaquil origin and Palmira since the bacterial growth that was evident after the filtration was more excellent than expected in the filters. Therefore, the application of filters is beneficial and efficient as long as the diatomaceous earth complies with a high filtering capacity, not to use flocculants to retain bacteria. Also, its design and structure are Properly equipped with specific materials to maintain the microorganisms present in the water resource, as well as not being used by strong water currents. Said statement was not fulfilled in the present investigation since the diatomaceous earth proved not to be effective enough for water purification.